(untitled) (Baghdad Science Journal, 2021)
The multimetric Phytoplankton Index of Biological Integrity (P-IBI) was applied throughout Rostov on Don city (Russia) on 8 Locations in Don River from April – October 2019. The P-IBI is composed from seven metrics: Species Richness Index (SRI), Density of Phytoplankton and total biomass of phytoplankton and Relative Abundance (RA) for blue-green Algae, Green Algae, Bacillariophyceae and Euglenaphyceae Algae. The average P-IBI values fell within the range of (45.09-52.4). Therefore, water throughout the entire study area was characterized by the equally "poor" quality. Negative points of anthropogenic impact detected at the stations are: Above the city of Rostov-on-Don (1 km, higher duct Aksai) was 38.57 in June, the lower inflow of the Temernik river which was 38.57- 41.42 in summer and below the spillway was 38.57 -34.28 in August. At these stations, samples with P-IBI values more than 56, characterizing water quality as "Fair", were not found in any of the observations. The negative effect on the water at the stations may be due to the influence of the closely located Aksai city and the impact of the Temernik River. In Russia P-IBI have not been used yet, so this study can be considered as the first study that’s conducted to assess the environmental status of the Don River by using the phytoplankton index of Biological Integrity and has developed scoring criteria of the Don River (P-IBI) and other watercourses of the south of Russia. The continuous monitoring relaying on the selection of the most suitable metrics score is recommended.